PENGEMBANGAN BUKU AJAR SASTRA ANAK BERBASIS BUDAYA LOKAL - Dhika Puspitasari; Yunita Furinawati; Muhamad Binur Huda (IKIP PGRI MADIUN, 2016)
As one kind of literature, children's literature has a mission to introduce the world of literature to children from an early age. Children's literature puts the viewpoint of children at the center of storytelling. However, it is not impossible if another mission also included the works of children's literature. Children's literature can be used as a means to teach the values of life, example and culture. So, teaches children's literature directly or indirectly two things at once, or even more. In the simplicity of children's literature stored complex dimensions. In addition, children's literature can also be used as a means to introduce the local culture to children. Children's literature-based local culture seeks to instill a love of cultural values that are around them. Unfortunately, Language and Literature Education curriculum Indonesia have not been up to elaborate teaching this genre. The course of children's literature is not supported by adequate instructional media. This research aims to develop children's literature-based instructional media for student PBSI IKIP PGRI Madiun.